Instrumentation & control : automatic process control (Primedia Workplace Learning, 2003)
v.1 --"To help maintain the efficiency of a process, variables such as temperature, pressure, level and flow are often controlled by automatic process control systems. Part of an operator's responsibility is using these control systems and understanding how they work."